The need for kidney biopsy in the management of side effects of target and immunotherapy - Fenoglio, Roberta; Cozzi, Martina; Del Vecchio, Giulio; Sciascia, Savino; Barreca, Antonella; Comandone, Alessandro; Roccatello, Dario (Frontiers in Nephrology, 2023)
The introduction of innovative therapies, resulting from revisiting cancer as a disease of the immune system, has changed the scenario of complications. These new classes of drugs, such as targeted therapies and immune checkpoint inhibitors, assure substantial advantages in cancer therapy, despite some side affecting various organs, including the kidney. Histological evaluations of kidney disorders induced by targeted/immunotherapy are limited. In this study we examined the histological features of patients treated with new cancer agents who underwent kidney biopsy for new onset kidney failure and/or urinary abnormalities. The cohort included 30 adult patients. The most frequently administered therapies were immunotherapy (30%), targeted therapy (26.7%), immunotherapy plus targeted therapy (13.3%), immunotherapy plus chemotherapy (13.3%), targeted therapy plus chemotherapy (16.7%). The most common histological finding was tubular interstitial nephritis (30%) that was associated with acute tubular necrosis in 4 cases, and thrombotic microangiopathy (23.3%). After kidney biopsy, 16 of the 30 patients were treated according to the histological diagnosis. Fourteen patients were treated with steroids. One patient with membranous nephropathy was treated with a single dose of rituximab. A patient with severe thrombotic microangiopathy requiring dialysis received a treatment with eculizumab for 3 months. Overall some renal response was obtained in all patients treated with glucocorticoids, while complete kidney response was achieved in the patient treated with rituximab. Cancer treatment was resumed without change in 21 out of 30 patients. Kidney biopsy is critical for the management of kidney toxicities and should be strongly encouraged for patients showing adverse kidney effects of novel cancer agents.